Expert evaluation of priority areas for implementation of medical and pharmaceutical technologies in Ukraine - M. M. Babenko; K. L. Kosiachenko (Zaporožskij Medicinskij Žurnal)
Aim. To analyze survey results of healthcare (НС) professionals on the status, problems and prospects of implementing medical and pharmaceutical technologies in Ukraine and their proper appraisal.